2019
DOI: 10.1093/mnras/stz1965
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency radio study of MACS clusters at 610 and 235 MHz using the GMRT

Abstract: Studies have shown that mergers of massive galaxy clusters produce shocks and turbulence in the intra-cluster medium, the possible event that creates radio relics, as well as the radio halos. Here we present GMRT dual-band (235 and 610 MHz) radio observations of four such clusters from the MAssive Cluster Survey (MACS) catalogue. We report the discovery of a very faint, diffuse, elongated radio source with a projected size of about 0.5 Mpc in cluster MACSJ0152.5-2852. We also confirm the presence of a radio re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 63 publications
(83 reference statements)
5
18
1
Order By: Relevance
“…At Band 4, with a restoring beam width of 5 we achieved a noise level of 7µ Jy beam −1 . Our new uGMRT Band 3 and Band 4 images are about a factor of ten deeper than the published VLA and GMRT images at the same frequency (Orrú et al 2007;Venturi et al 2013;Paul et al 2019).…”
Section: Results: Radio Continuum Imagesmentioning
confidence: 47%
See 1 more Smart Citation
“…At Band 4, with a restoring beam width of 5 we achieved a noise level of 7µ Jy beam −1 . Our new uGMRT Band 3 and Band 4 images are about a factor of ten deeper than the published VLA and GMRT images at the same frequency (Orrú et al 2007;Venturi et al 2013;Paul et al 2019).…”
Section: Results: Radio Continuum Imagesmentioning
confidence: 47%
“…It is known to host a giant ∼ 2.1 Mpc large radio halo at the cluster center and a 1.5 Mpc relic to the north-east. (Giovannini et al 1999;Govoni et al 2001a,b;Orrú et al 2007;Venturi et al 2013;Pearce et al 2017;George et al 2017;Paul et al 2019). With deep VLA observations, Pearce et al (2017) found three new faint radio relics (namely, R2, R3, and R4) in this system, see Fig.…”
Section: Abell 2744mentioning
confidence: 82%
“…For ZwCl 1742.1+3306, the observations were not sufficient to be sure of its nature. However, Paul et al (2019) confirmed the presence of a significant extra diffuse emission surrounding the BCG at the centre of the cluster MACS J1931.8−2634 using GMRT radio observations at 235 and 610 MHz, and we therefore now consider this source as a confirmed mini-halo. We retain the total flux density from Giacintucci et al (2014a) as Paul et al (2019) found the total flux density at 235 and 610 MHz and not at 1.4 GHz.…”
Section: Cluster Samplesupporting
confidence: 52%
“…For example, the relic at Abell 2744 (e.g. Govoni et al 2001;Eckert et al 2016;Pearce et al 2017;Paul et al 2019) reaches a surface brightness of the order of tens of mJy beam −1 at 1.4 GHz, which would require an acceleration efficiency of η ∼ 1 in our L/4 turbulence.…”
Section: S U M M a Ry A N D C O N C L U S I O N Smentioning
confidence: 99%